MANAGEMENT OF LINEN HOUSEKEEPING IN THE PREMIERE HOTEL PEKANBARU - Santi Ariska; Andi M. Rifiyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research was to identified and analyzed of linen management process used in housekeeping department at The Premiere Hotel Pekanbaru.This research used theory of Usin S Artyasa (2006 : 114) to explanation about steps in management of room linen, the good management is done by : control and supervision, stock, improvement, control of linen, and standard washing.The method of this research is using kualitatif analysis method. Analysis in the research based in literature, observation, and direct interview with informan who consider able to provide informationrelation to problem examined.Room occupancy is at its highest level is the result of management were able to sufficient needs of operational of housekeeping department.Keywords : linen management